The Influence of Achievement Motivation on Employee Job Performance at Pandora Corp: Pengaruh Motivasi Berprestasi Terhadap Prestasi Kerja Karyawan pada Pandora Corp - Imam Sulaiman; M. Ilham Wardhana Haeruddin; Abdi Akbar; Agung Widhi Kurniawan; Tenri Sayu Puspitaningsih Dipoatmodjo (Journal of Management Specialists, 2023)
This study aims to determine how achievement motivation affects employee performance at Pandora Corp. The population in this study were all 34 Pandora Corp employees, so a saturated sample was used to take the population as a sample. The data collection technique was carried out using the questionnaire method. The data analysis technique used is simple linear analysis and correlation coefficient analysis (R) using the IBM Statistical for Product and Service (SPSS) Version 25 program. The results showed that achievement motivation statistically affects employee work performance at Pandora Corp which has been proven by the significance value in the regression test t-count value greater than the t-table value, namely 6,053> 2,037. Therefore HI is accepted and it can be said that there is a strong influence between achievement motivation (X) on work performance (Y) of Pandora Corp employees. When viewed from the statistical results of the correlation coefficient (R) of 0.731, it can be interpreted that achievement motivation on work performance has a strong relationship and also the coefficient of determination of 0.534 means that achievement motivation has an influence on work performance by 53%, the remaining 47% is influenced by other variables not examined in this study